Penanaman Nilai-Nilai Karakter Islam Mewujudkan Generasi Qurani Di Madrasah Ditinjau Dari Aksiologi Filsafat Pendidikan Islam - Musyafak; M. Sugeng Sholehuddin (CV Edujavare Publishing, 2023)
This article discusses efforts to instill Islamic character values as the main strategy in forming the Quranic generation in the madrasa environment, seen from the axiological perspective of Islamic educational philosophy. Emphasis on Islamic character education is considered a crucial foundation for producing individuals who are not only academically competent, but also have strong morality in accordance with Islamic teachings. This research aims to analyze the process of instilling Islamic character values in madrasas with a focus on the achievements of the Quranic generation. The approach used in this research is axiology, which is the study of values, in the context of Islamic educational philosophy. The research method used is a descriptive analytical method with a qualitative approach. Data was collected through observation, interviews and analysis of documents related to the curriculum and extracurricular activities at madrasas. The research respondents involved madrasa teachers and students who were involved in the Islamic character cultivation program. The research results show that madrasas have concrete efforts in instilling Islamic character values. This process involves religious learning, developing positive attitudes, and applying Quranic values in daily life. However, there are several challenges faced, such as a lack of adequate resources and support. This research contributes to further understanding of the role of instilling Islamic character values in forming the Quranic generation in madrasas. The practical implications of the results of this research can be used as a guide for developing madrasa curricula that are more effective in instilling Islamic character values, as well as as a basis for improving Islamic education policies.